2019
DOI: 10.1037/vio0000132
|View full text |Cite
|
Sign up to set email alerts
|

Applying the social–ecological framework to explore bully–victim subgroups in South Korean schools.

Abstract: Objective: The present study sought to identify the structure of South Korean student bully and victim groups based upon longitudinal data, and the association of groups with socialecological based factors at the individual (age, sex, father and mothers' educational status, household income, aggression, depression, smoking, drinking, type of family structure), family (neglect, abuse), friend/peer (peer relationships, number of delinquent friends), and school (school activity, school rules, teacher relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
0
12
0
7
Order By: Relevance
“…Research showed that in a group of South African adolescents from communities of lower socioeconomic status, the majority have encountered violence at home, in school, and in community [4]. Male adolescents are more likely than their female counterparts to encounter violence victimisation in school and community [7], or engage in aggressive behaviours and violence perpetration [17][18][19].…”
Section: Risk Factors For Victimisation and Perpetrationmentioning
confidence: 99%
See 3 more Smart Citations
“…Research showed that in a group of South African adolescents from communities of lower socioeconomic status, the majority have encountered violence at home, in school, and in community [4]. Male adolescents are more likely than their female counterparts to encounter violence victimisation in school and community [7], or engage in aggressive behaviours and violence perpetration [17][18][19].…”
Section: Risk Factors For Victimisation and Perpetrationmentioning
confidence: 99%
“…Moreover, one's family structure, particularly residing in a single-parent household is significantly associated with both violence victimisation and perpetration in youth [13,17]. In South Africa, partly due to the HIV/ AIDS epidemic, approximately 3.5 million children are orphaned [26].…”
Section: Risk Factors For Victimisation and Perpetrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Meski demikian, ekologi sosial juga bisa berlaku sebaliknya, mengubah seseorang menjadi berperilaku buruk, saat tidak dikondisikan dengan baik. Hal ini sering ditemui pada perilaku merokok, minum minuman beralkohol (Chen, Ho, Leung, Wang, & Lam, 2019) (Wang, Tian, & Huebner, 2019), maupun kasus perudungan pada anak (Hong, Kim, & Hunter, 2019) (Kim et al, 2018).…”
Section: Perubahan Perilakuunclassified